Inventory of Mangrove Species in Nagari Pilubang, Sungai Limau District, Padang Pariaman Regency, West Sumatra - Taufiq, Muhammad Afif; Putri, Irma Leilani Eka; Kardiman, Reki; Satria, Rijal (Jurnal Serambi Biologi, 2024)
Mangroves have two meanings, the first refers to plant communities or forests that are able to tolerate salinity or saltwater conditions (aquifers). While the second refers to individual plant species, mangrove species inventories are also important in a global context, given the role these ecosystems play in storing carbon and protecting coasts from storms and erosion. This study aims to inventory of mangrove species in Nagari Pilubang, Sungai Limau District, Sungai Limau Regency, West Sumatra. This study used the Spot Check method. The results of the inventory of mangrove species at the observation location showed that there were 17 species from 16 families that make up the mangrove forest observed. True mangroves include Sonneratia caseolaris, Nypa fruticans, Acrostichum aureum, Acanthus ebracteatus, Acanthus ilicifolius, while the following mangroves include Hibiscus tiliaceus, Derris trifolia, Dolichandrone spathacea, Pandanus tectorius, Cerbera manghas, Melastoma candidum, Ardisia elliptica, Glochidion littorale, Barringtonia asiatica, Calophyllum inophyllum, Morinda citrifolia, and Wedelia biflora.